Social communication assessment during post-traumatic amnesia and the post-acute period after traumatic brain injury. (24th August 2017) - Steel, Joanne; Ferguson, Alison; Spencer, Elizabeth; Togher, Leanne
ABSTRACT: Background : Social communication impairment is a persisting and debilitating consequence of traumatic brain injury (TBI). However, there has been little empirical speech-language pathology (SLP) study focusing on the early stage of recovery after TBI, including during post-traumatic amnesia (PTA). This research reports on social communication presentation and recovery during late PTA and the post-acute period, assessed with standardized measures. Method : Using mixed-methods case study research, four participants with severe TBI were assessed with social communication assessment measures over the later stages of PTA and/or at PTA emergence, and at follow-up three months later. Assessment tools included the Measure of Cognitive Linguistic Abilities Family Questionnaire, the La Trobe Communication Questionnaire and The Profile of Pragmatic Impairment in Communication and included patient and friend/family perspectives. Results : It was possible to identify a profile of social communication disorder on SLP measures for participants during PTA that persisted at follow-up, but with decreased severity. Self and friend/family member ratings of social communication indicated an increased awareness of social difficulty at three months after PTA emergence. Conclusion : Findings provided information about presentation and course of recovery of social communication ability for participants in the early stage of rehabilitation after TBI. These findings have implications for timing and methods of SLP assessment during PTA.